2015
DOI: 10.1111/cpr.12226
|View full text |Cite
|
Sign up to set email alerts
|

SL4, a chalcone‐based compound, induces apoptosis in human cancer cells by activation of the ROS/MAPK signalling pathway

Abstract: These data demonstrate that SL4 induced apoptosis in human cancer cells through activation of the ROS/MAPK signalling pathway, suggesting that it may be a novel lead compound, as a cancer drug candidate, with polypharmacological characteristics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 41 publications
3
12
0
Order By: Relevance
“…Chalcones are promising lead antitumor/chemopreventive drugs due to three different activities: antioxidant, cytotoxic, and apoptosis induction (2). Several studies with murine xenograft models have shown that administration of chalcones significantly reduced the tumor volume by inducing apoptosis (3)(4)(5)(6)(7)(8)(9)(10). The tumor specificity of chalcones has been reported in comparing sensitivity of hepatocarcinoma HepG2 cells to normal liver AML12 cells (11); osterosarcoma to bone marrow and smallintestinal epithelial cells (12); murine acute lymphoblastic leukemia cells L-1210 to normal human lymphocytes (13); and human prostate cancer cells PC3 and DU145 to normal human prostate epithelial cells (14).…”
mentioning
confidence: 99%
“…Chalcones are promising lead antitumor/chemopreventive drugs due to three different activities: antioxidant, cytotoxic, and apoptosis induction (2). Several studies with murine xenograft models have shown that administration of chalcones significantly reduced the tumor volume by inducing apoptosis (3)(4)(5)(6)(7)(8)(9)(10). The tumor specificity of chalcones has been reported in comparing sensitivity of hepatocarcinoma HepG2 cells to normal liver AML12 cells (11); osterosarcoma to bone marrow and smallintestinal epithelial cells (12); murine acute lymphoblastic leukemia cells L-1210 to normal human lymphocytes (13); and human prostate cancer cells PC3 and DU145 to normal human prostate epithelial cells (14).…”
mentioning
confidence: 99%
“…The IC 50 values were 1.1 ± 0.2 μM, 0.5 ± 0.1 μM, 1.3 ± 0.1 μM and 0.3 ± 0.1 μM for MCF-7, MDA-MB-231, MDA-MB-436 and Bcap37 cell lines, respectively. These values are lower than our previously reported IC 50 (16.9 ± 2.4 μM) for SL4 on normal MCF-10A breast cells16. Given their sensitivity to SL4 and their genotype-phenotype characteristics, we selected MCF-7 (ER+, PR+, HER2-, and p53 wild type) and MDA-MB-231 (ER-, PR-, HER2-, and p53 mutation) for subsequent experiments.…”
Section: Resultsmentioning
confidence: 82%
“…SL4 was administered at a dose of 2.5 or 5.0 mg/kg, in accordance with our previous report16. As shown in Fig.…”
Section: Resultsmentioning
confidence: 83%
See 1 more Smart Citation
“…C-caspase-9 can induce the cleavage of procaspase-3 (c-caspase-3), which induces apoptosis of cells (21). The cleavage of procaspase-3 caused by c-caspase-9 can be inhibited by Survivin, whose function can be attenuated by Smac in the cytoplasm (22,23). The results of western blot analysis in the present study indicated that chrysotoxene induced the apoptosis of HepG2 cells by promoting the release of Smac and Cytochrome c from the mitochondria to the cytoplasm, downregulating Survivin and Bcl-2 protein levels, and upregulating Bax, Apaf-1, c-caspase-9 and c-caspase-3 protein levels (Figs.…”
Section: Discussionmentioning
confidence: 99%